On the Adjacency, Laplacian, and Signless Laplacian Spectrum of Coalescence of Complete Graphs - S. R. Jog; Raju Kotambari (Journal of Mathematics)
Coalescence as one of the operations on a pair of graphs is significant due to its simple form of chromatic polynomial. The adjacency matrix, Laplacian matrix, and signless Laplacian matrix are common matrices usually considered for discussion under spectral graph theory. In this paper, we compute adjacency, Laplacian, and signless Laplacian energy (Q energy) of coalescence of pair of complete graphs. Also, as an application, we obtain the adjacency energy of subdivision graph and line graph of coalescence from its Q energy.